PENGARUH PENYULUHAN DENGAN MEDIA PHANTOM TERHADAP PENGETAHUAN IBU HAMIL MENGENAI ASI EKSKLUSIF DI BABYSPA ALKHANSA KOTA MAGELANG - Tehuayo, Sakina Aulia; Pratiwi, Rini (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Background: Exclusive breastfeeding is the provision of breast milk alone to infants aged 0-6 months by the mother without any additional food. Exclusive breastfeeding coverage in Magelang city has decreased from the previous year and has not reached the expected target. The intervention that can be done is counseling using phantom media to increase the knowledge of pregnant women. Objective: To determine the effect of counseling with phantom media on the knowledge of pregnant women about exclusive breastfeeding at Babyspa Alkhansa Magelang City. Methods: This type of research is quantitative using Pre-experimental approach with one group pretest and posttest design. The research subjects used were 30 pregnant women who were selected using purposive sampling. Counseling was conducted using phantom media as props and questionnaires to measure the level of knowledge of pregnant women. The data analysis used was the Wilcoxon test. Results: The results showed that there was an effect on increasing the knowledge of pregnant women after being given counseling using phantom media (p-value = 0.000 <0.05). Conclusion: Counseling provided using phantom media as props is effective in increasing the knowledge of pregnant women about exclusive breastfeeding. Keywords: Exclusive Breastfeeding, Knowledge, Pregnant Women, Phantom Media